Characterization and possible valorization of grape skin in extruded crisps - Silvia Mironeasa; Mădălina Ungureanu-Iuga; Costel Mironeasa; Mircea-Adrian Oroian; Gelu-Marius Rotaru (Future Foods)
Grape skin byproduct valorization in extrudates for human nutrition is a great opportunity with many health, environmental, and economic benefits. This paper explored the impact of red and white grape skins on corn flour and extruded crisp quality. Flour mixtures composition was assessed along with extruded products' properties in terms of digestibility, polyphenols, texture, physical, and functional properties. Grape skin increased (p < 0.05) the content of nutrients (from 7.20 to 9.53 % protein, from 1.32 to 3.36 % fat, from 6.74 to 28.10 % for fiber) in the flour mixtures and changed the color depending on the addition level and grape skin type. Final product quality was affected significantly (p < 0.05) by grape skin: the expansion index (from 3.70 to 2.68), pore size, and functional properties decreased as the level was higher. White grape skin decreased (p < 0.05) the texture parameters (5.82 to 3.63N/s for crispness), while the opposite trend was observed for the red type (3.82 to 6.20N/s for crispness). Grape skin came with an intake of polyphenols like myricetin, p-coumaric acid, and determined significant changes (p < 0.05) in starch digestibility. Acceptable scores for the sensory texture parameters were obtained even at 40 % red grape skin content, but considering the characteristics evaluated, an addition level of 30 % would be recommended. The novelty lies in the complete and applied approach to the valorization of high amounts of grape skin (up to 40 %) to improve the nutritional and functional properties of expanded corn crisps, providing concrete data for optimizing the process on an industrial scale.